Implementasi Karakter Religius di MA Pertanian Kota Madiun dalam Perspektif Kedisiplinan Siswa Keterlibatan Guru dan Lingkungan Sekolah - Mustafid Mustafid (BASICA, 2023)
Mustafid, S.Pd. 2025. "Implementation of Religious Character at MA Pertanian Kota Madiun in the Perspective of Student Discipline, Teacher Involvement, and School Environment". Thesis, Master’s Postgraduate Program (S2) in Islamic Religious Education, Sunan Giri Islamic Institute, Ponorogo. Supervisors: (I) Dr. Ahmad Syafi’i S.J., M.S.I; (II) Dr. Samsudin, S.Pd.I, M.Pd. This research is motivated by the importance of fostering religious character in schools as the moral and spiritual foundation for students in facing the challenges of the modern era. MA Pertanian Kota Madiun is one of the educational institutions that strives to internalize religious values through exemplary behavior, habituation, and religious activities. Based on this background, the study aims to describe the implementation of religious character at MA Pertanian Kota Madiun from the perspective of student discipline and teacher involvement, to analyze the role of the school environment in supporting the implementation of religious character, and to identify the supporting and inhibiting factors that influence its implementation. This study employs a qualitative approach with a descriptive research type. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, and students. Data analysis was carried out through three stages: data reduction, data presentation, and conclusion drawing. The validity of the data was tested using triangulation of sources, techniques, and time to ensure the accuracy of the research results. The findings indicate that the implementation of religious character at MA Pertanian Kota Madiun has been carried out quite well through religious activities such as Qur’an recitation (tadarus), morning prayers, dzuhur congregational prayers, and the habituation of disciplined and courteous behavior. Teacher involvement plays an important role in providing good examples and guiding students in religious activities. The school environment also contributes positively by creating a religious atmosphere and implementing regular programs that support character development. The main supporting factors include school policies that promote religious values and the enthusiasm of teachers in guiding students, while the inhibiting factors include uneven student discipline, lack of consistency in implementation, and the influence of less conducive external environments. The study concludes that the success of implementing religious character requires continuous synergy among teachers, students, and the school environment.